2022
DOI: 10.1017/s0950268822000826
|View full text |Cite
|
Sign up to set email alerts
|

Improper handling of vomitus as a risk factor in the human norovirus outbreak in a kindergarten in Wuyi County, Zhejiang Province, China

Abstract: This study investigated an outbreak in a kindergarten in Wuyi County of acute gastroenteritis concerning a large number of students and teachers. We performed a case-control study, and collected information on the layout of the school, symptoms, onset time of all cases and vomiting sites. A total of 62 individuals fit the definition of probable cases; among these, there were 19 cases of laboratory-confirmed norovirus infection. Nausea and vomiting were the most common symptoms in the outbreak. Seven student no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Waterborne and foodborne outbreaks are more likely to result in larger-scale infections and outbreaks within populations ( 30–32 ). While there are still reports of small-scale outbreaks caused by aerosol transmission ( 22 , 33 ). During the early stages of Norovirus infection, vomitus can contain a high viral load, facilitating its spread in enclosed dormitories, public spaces, and on surfaces of public objects ( 24 , 34 ), aerosols which are easily formed can be inhaled, leading to infection ( 33 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Waterborne and foodborne outbreaks are more likely to result in larger-scale infections and outbreaks within populations ( 30–32 ). While there are still reports of small-scale outbreaks caused by aerosol transmission ( 22 , 33 ). During the early stages of Norovirus infection, vomitus can contain a high viral load, facilitating its spread in enclosed dormitories, public spaces, and on surfaces of public objects ( 24 , 34 ), aerosols which are easily formed can be inhaled, leading to infection ( 33 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there are still reports of small-scale outbreaks caused by aerosol transmission ( 22 , 33 ). During the early stages of Norovirus infection, vomitus can contain a high viral load, facilitating its spread in enclosed dormitories, public spaces, and on surfaces of public objects ( 24 , 34 ), aerosols which are easily formed can be inhaled, leading to infection ( 33 , 35 , 36 ). Studies in the United States, Germany, and Australia have demonstrated that the outbreak and detection rate of norovirus infection have decreased significantly through non-pharmaceutical interventions such as closing schools, restaurants, and other public places, promoting social distancing, and raising personal hygiene awareness since the COVID-19 outbreak in 2020 ( 37–39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, similar to parents [ 10 ], most staff members lack accurate understanding regarding the duration and symptoms of the disease, which may lead to an increased possibility of children attending classes while ill. Finally, Improper handling of children's vomit can undoubtedly lead to secondary transmission [ 3 ]. Therefore, it is crucial to pay close attention to students with gastrointestinal symptoms during morning screenings in order to minimize the occurrence of vomiting in classrooms and prevent large-scale outbreaks caused by NoV infections [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study encompassing 45 countries globally revealed that 17.7% of pediatric gastroenteritis cases were attributed to NoVs, thereby urgently highlighting its role as the second leading cause of AGE [ 2 ]. Genogroups GI and GII of NoVs primarily contribute to acute gastroenteritis episodes [ 3 ], particularly in southern China. Furthermore, the virus's highly contagious nature and survival ability are accountable for its widespread transmission.…”
Section: Introductionmentioning
confidence: 99%